Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

how do you solve this?


How Do You Solve This class=

Sagot :

[tex]x^2-3x-4=0\\\\x^2-2x\cdot\frac{3}{2}=4\ \ \ /+(\frac{3}{2})^2\\\\x^2-2x\cdot\frac{3}{2}+(\frac{3}{2})^2=4+(\frac{3}{2})^2\\\\(x-\frac{3}{2})^2=4+\frac{9}{4}\\\\(x-\frac{3}{2})^2=\frac{16}{4}+\frac{9}{4}\\\\(x-\frac{3}{2})^2=\frac{25}{4}\\\\x-\frac{3}{2}=\pm\sqrt\frac{25}{4}[/tex]

[tex]x-\frac{3}{2}=\pm\frac{\sqrt{25}}{\sqrt4}\\\\x-\frac{3}{2}=\pm\frac{5}{2}\\\\x-\frac{3}{2}=-\frac{5}{2}\ or\ x-\frac{3}{2}=\frac{5}{2}\\\\x=-\frac{5}{2}+\frac{3}{2}\ or\ x=\frac{5}{2}+\frac{3}{2}\\\\x=-\frac{2}{2}\ or\ x=\frac{8}{2}\\\\x=-1\ or\ x=4[/tex]
AL2006
Why not simply factor the left side ?

(x - 4) times (x + 1) = 0

This equation is true if either factor is zero.

(x - 4) = 0
x = 4

(x + 1) = 0
x = -1
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.